Route of biofuel production from macadamia nut shells: effect of parameters on the particles mixing index in fluidized beds - Mendonça, Bárbara; Mantegazini, Diunay; Nariyoshi, Yuri; Bacelos, Marcelo Silveira (Brazilian Journal of Production Engineering, 2023)
Pyrolysis of macadamia nut shells (MNS) in a fluidized bed reactor has excellent potential to produce bio-oil. High heat transfer rates and uniform temperature in the fluidized bed can be achieved due to effective gas-solid contact in the reactor. However, binary mixtures can lead to the segregation of particles, which negatively affects heat and mass transfer in such a reactor. Therefore, a 2³ statistical experimental design was used to assess the effects of parameters (i.e., air velocity, particle diameter ratio, and mass fraction of MNS) on the mixing index of the bed of MNS and sand. Among the analyzed factors, only DMNS/DS and V/VMF influenced the mixing index (Im) within a confidence interval of 95%. Based on statistical data analysis, an air velocity 20% above the minimum fluidization and particle diameter ratio (DMNS/DS) smaller than 3 results in uniform particle mixing in the bed (i.e., reaching ideal mixing index values). Moreover, the experimental results indicate that fluidized be used for biofuel production from Macadamia nut Shells.
Keywords: Biomassa; Fluidodinâmica; Energia; Segregação; Sustentabilidade